2020
DOI: 10.1096/fj.201902127r
|View full text |Cite
|
Sign up to set email alerts
|

The tripartite interaction of phosphate, autophagy, and αKlotho in health maintenance

Abstract: Aging-related organ degeneration is driven by multiple factors including the cell maintenance mechanisms of autophagy, the cytoprotective protein αKlotho, and the lesser known effects of excess phosphate (Pi), or phosphotoxicity. To examine the interplay between Pi, autophagy, and αKlotho, we used the BK/BK mouse (homozygous for mutant Becn1 F121A ) with increased autophagic flux, and αKlothohypomorphic mouse (kl/kl) with impaired urinary Pi excretion, low autophagy, and premature organ dysfunction. BK/BK mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 88 publications
(222 reference statements)
1
35
0
Order By: Relevance
“…Accumulation of misfolded proteins further contributed to cell senescence and potentiated renal fibrosis 158 . α-Klotho, a type 1 transmembrane protein, is originally identified as an aging suppressor and can be released into circulation and exert multiple effects on target organs.α-Klotho expression deficiency was shown to be responsible for endothelial dysfunction, microangiopathy and fibrosis 168 . Similarly, a recent article showed that αKlotho activation attenuated renal fibrosis, protected renal cells from oxidative stress and suppressed the progression of AKI to CKD through the upregulation of autophagy flux, which was reversed in α-Klotho deficiency mouse model 169 .…”
Section: Kidney Fibrosis and Autophagymentioning
confidence: 99%
“…Accumulation of misfolded proteins further contributed to cell senescence and potentiated renal fibrosis 158 . α-Klotho, a type 1 transmembrane protein, is originally identified as an aging suppressor and can be released into circulation and exert multiple effects on target organs.α-Klotho expression deficiency was shown to be responsible for endothelial dysfunction, microangiopathy and fibrosis 168 . Similarly, a recent article showed that αKlotho activation attenuated renal fibrosis, protected renal cells from oxidative stress and suppressed the progression of AKI to CKD through the upregulation of autophagy flux, which was reversed in α-Klotho deficiency mouse model 169 .…”
Section: Kidney Fibrosis and Autophagymentioning
confidence: 99%
“…Four μm sections of paraffin-embedded kidney or cryosections were used for immunohistochemistry following protocols previously published ( Li et al., 2020 ; Shi et al., 2020 ). For non-nuclear protein staining, paraffin-embedded kidney sections were de-waxed and rehydrated, then heated in a microwave in 10 mM citrate buffer (pH 6.0) for 30 min (20 min in boiling conditions) to retrieve antigens.…”
Section: Methodsmentioning
confidence: 99%
“…Aging is an inevitable multi-organ deterioration initiated and accelerated by multiple factors. We have shown that Klotho deficiency and excess phosphate (Pi) have detrimental effects on aging ( Fernandez et al., 2018 ; Shi et al., 2020 ). Compelling observational and animal studies showed that phosphotoxicity is associated with reduced longevity in several species ( Kuro-O, 2010 ; Shi et al., 2020 ) and causes severely abnormal metabolism and ill effects on bone, kidney, cardiovasculature, and other organs in chronic kidney disease (CKD) ( Kestenbaum et al., 2005 ; Tonelli et al., 2005 ; John et al., 2011 ; Calvo et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations